Pelatihan Inventarisasi Aset Desa Dan Pengembangan BUMDes Untuk Penguatan Ekonomi Desa Di Desa Saba Kecamatan Blahbatu Kabupaten Gianyar - Bandiyah, Bandiyah (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2019)
The training activity on village asset inventory and development of Village-Owned Enterprises (BUMDesa) aims to provide knowledge insights to the Saba Village apparatus and scientific skills to be able to inventory potential assets belonging to the village in order to develop Village Owned Enterprises (BUMDesa). The activity was carried out in the form of training with a workshop approach, discussion and tutorial videos on asset inventories along with comprehensive analysis of solutions to the problem of developing BUMDesa. The results of this service activity include. First, the Saba Village apparatus gained an understanding of village assets and potential that could be developed into a village economy. Secondly, the village apparatus was very enthusiastic and eager to establish BUMDesa. Third, the Sipedas tutorial method helps provide convenience as well as a skill in conducting an asset inventory. Third, helping to solve the problem of assets in Saba Village which had previously been a conflict between communities and has now become clear.Keywords: Village Assets, BUMDesa, Village Economy, Training, Saba